Effects of advanced injection strategies on the in-cylinder air–fuel homogeneity of diesel engines. (February 2015) - Dimitriou, Pavlos; Peng, Zhijun; Wang, Weiji; Gao, Bo; Wellers, Matthias
The air–fuel mixing quality in the combustion chamber of a diesel engine is very critical for controlling the ignition and the combustion quality of direct-injection diesel engines. With a view to understanding the air–fuel mixing behaviour and the effect of the mixture quality on the emissions formation, an innovative approach with a new quantitative factor of the in-cylinder air–fuel homogeneity, called the homogeneity factor, was used, and its characteristics under various injection conditions were analysed with computational fluid dynamics simulations. By investigating the effect of advanced injection strategies on the homogeneity of the mixture and the emissions production, the study suggested that the homogeneity factor is greatly affected by the pulse number of injections, the injection timing and the dwell angle between two injections. The more advanced the injection taking place in the cylinder, the earlier the air–fuel mixing quality reaches a high level. Although the homogeneity factor is not sufficiently precise by itself to reflect the emissions formation, the results demonstrated that most often, the higher the homogeneity available in the cylinder, the more nitrogen oxides and the less soot were formed.